1995
DOI: 10.1111/j.1752-1688.1995.tb03390.x
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF GULLY‐CONTROL STRUCTURES IN THE RIO NUTRIA WATERSHED, ZUNI RESERVATION, NEW MEXICO1

Abstract: During the latter part of the 19th century and the early part of the 20th century, a major cycle of erosion, arroyo cutting, and gullying occurred in the southwestern United States. Since this erosion cycle began, many projects to control erosion, such as the Civilian Conservation Corps projects in the 1930s, were initiated. However, in the Southwestern United States few studies have documented the effect of these structures in reducing erosion or their effect on gully systems. As part of a watershed rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
3
19
1
Order By: Relevance
“…In many arroyos studied in the Southwest in the late twentieth century, aggradation was observed in the lower reaches, while headcutting was still active in upstream reaches and tributaries (Gellis, 2002;Gellis et al, 1991Gellis et al, , 1995. These downstream and upstream channel changes were also observed in the arroyos studied here (Figs.…”
Section: Stage Of Southwestern Arroyos In the Late Twentieth Centurysupporting
confidence: 58%
See 1 more Smart Citation
“…In many arroyos studied in the Southwest in the late twentieth century, aggradation was observed in the lower reaches, while headcutting was still active in upstream reaches and tributaries (Gellis, 2002;Gellis et al, 1991Gellis et al, , 1995. These downstream and upstream channel changes were also observed in the arroyos studied here (Figs.…”
Section: Stage Of Southwestern Arroyos In the Late Twentieth Centurysupporting
confidence: 58%
“…The arroyo cycle described in the model is initiated by the headward migration of headcuts. These sequential arroyo changes generally proceed over time from the lower reaches of the arroyo to upstream reaches, but they can vary locally due to the infl uence of large tributaries, large fl oods (Pederson, 2000), bedrock controls, and human factors, such as impoundments (Gellis et al, 1995). While arroyo incision in many areas has been attributed to the headward migration of headcuts (Cooke and Reeves, 1976), this does not occur in all arroyos (Cooke and Reeves, 1976;Hereford, 2002).…”
Section: Arroyo Cyclementioning
confidence: 98%
“…On the Zuni Reservation in New Mexico, Gellis et al (1995) observed that only five of 23 brush structures were damaged during his study and Norton et al (2002) found that brush structures successfully endured 25-year recurrence interval flooding, with larger floods beneficially redepositing the woody material down the channel. Though at a different scale and setting, some hydraulic qualities of woody debris in larger perennial streams should be applicable across a wide range of scales and environments (Montgomery and Piegay, 2003).…”
Section: Brush Checkdams Versus Rock Liningsmentioning
confidence: 95%
“…For example, arroyo erosion has seriously damaged Zuni and other Southwest land during the past century. However, this is likely due to a combination of climate change, intrinsic geomorphic factors and natural erosion cycles, and later historic land-use problems (e.g., Balling and Wells, 1990;Gellis et al, 1995;Hart, 1995;Knox, 2001), rather than to traditional Zuni farming. In fact, traditional Zuni agricultural management has likely promoted erosion control and soil conservation (Stewart and Donnelly, 1943;Bull, 1997;Norton et al, 2002).…”
Section: Long-term Soil Change and Relevance To Sustainable Land Usementioning
confidence: 99%